Methods and tools of project management used in production organizations - A. A. Artamoshkina; S. M. Sycheva; E. A. Khalimon (Вестник университета, 2023)
Project management is an important part of all business processes, as the future of the enterprise depends on the success of the implementation of project activities. The article discusses the main methods of project management used in production organizations: Agile, Kanban, Waterfall and Scrum. The following general scientific research methods were used: analysis, generalization, classification, description. The purpose of the article is to popularize the application of the project approach in the manufacturing sector of the economy by systematizing the main methods of project management for their further use by companies. Examples of the methods application in Russian production organizations – JSC “Litmashdetal” and the publishing house “MIF” are presented. The main digital project management tools used in production and companies are demonstrated, with the help of which the effective implementation of the project approach is possible. Such an approach can be implemented in production if the principles of the method used are observed in the process of its realization in the company.